ANALYSIS FOCAL MECHANISM OF MICRO EARTHQUAKE IN WAYANG WINDU GEOTHERMAL FIELD TO PREDICT THE PERMEABILITY ZONE - Sultan - NIM: 22616004 , Rhamadhana
Micro seismic monitoring at the Wayang Windu geothermal field is conducted to determine changes in subsurface conditions due to steam exploitation in the field. The micro seismic data used in this study was recorded by 15 seismometer stations scattered around the field in the period January to June 2016. Analysis of the seismic source mechanism is done by running the full waveform method based on inversion of the moment tensor. The software used is ISOLA-GUI, which can determine the moment tensor solution in the form of fault orientation and the type of source mechanism. Filter process is performed to eliminate the high frequency components. Furthermore, synthetic modeling conducted to estimate the Green Function, which is indicated by the best fittings between synthetic waveform curves and observation data. The moment tensor solution obtained for 34 micro-earthquake sources in field, showed the fault orientation and source mechanism that were ready to be further analyzed. The fault orientation in the northern part of the research location has a dominant fracture direction of N165oE with a dip of 30o - 90o. While the fault orientation found in the southern has a dominant fracture direction of N90oE with a dip of 20o - 80o. The obtained moment tensor solution has the same orientation with a strike-slip fault structure, as measured by previous study in this field. The dominant source mechanism of micro earthquake in this filed is a non-double-couple type which has large CLVD and volumetric components. The volumetric component indicates changes in pores in subsurface due to exploitation activities. Thus, the dominant source of micro earthquake in this field comes from implosive sources or closing cracks in the North and South, which probably indicates that permeability at the study site has decreased due to exploitation activities.